Bank relationships and firms' financial performance: the Italian experience - Annalisa Castelli; Gerald P. Dwyer; Iftekhar Hasan (Bank of Finland, 2009)
We examine the connection between the number of bank relationships and firms performance using a unique data set on Italian small firms for which banks are a major source of financing. Our evidence indicates that return on equity and return on assets decrease as the number of bank relationships increases, the effects being stronger for small firms than for large firms. We also find that the ratio of interest expense to assets increases as the number of relationships increases. Particularly for small firms, these results are consistent with finding that suggest that having fewer bank relationships reduces the information asymmetries and agency problems and outweighs the hold-up problems.
URN:NBN:fi:bof-20140807149
Keywords: 330